Potato tuber UDP-Glucose: Protein transglucosylase catalyzes its own glucosylation - Ardila, F.J. (1992)
Potato (Solanum tuberosum L.) tuber UDP-glucose:protein transglucosylase (UPTG) (EC 2.4.1.112) is involved in the first of a two-step mechanism proposed for protein-bound α-glucan synthesis by catalyzing the covalent attachment of a single glucose residue to an acceptor protein. The resulting glucosylated 38-kilodalton polypeptide would then serve as a primer for enzymic glucan chain elongation during the second step. In the present report, we describe the fast protein liquid chromatography purification of UPTG from a membrane pellet of potato tuber. An apparently close association of UPTG, phosphorylase, and starch synthase was observed under native conditions during different purification steps. Enrichment of a 38-kilodalton polypeptide was found throughout enzyme purification. It is now shown that the purified UPTG, with an apparent molecular mass of 38 kilodaltons, undergoes self-glucosylation in a UDP-glucose- and Mn2+-dependent reaction. Therefore, it is concluded that UPTG is the enzyme and at the same time the priming protein required for the biogenesis of protein-bound α-glucan in potato tuber.